Infestation of coconut eriophyid mite, Aceria guerreronis Keifer in Konkan region of Maharashtra (The Journal of Plant Protection Sciences, 2020)
The coconut eriophyid mite was reported to cause damage in coconut plantations in Konkan region of Maharashtra from January 2002. Three orchards from this area were surveyed to record infestation level of this pest in April and October of 2004 and March 2005. The survey indicated that the infestation was higher in Thane district followed by Sindhudurg district.
Keywords: Coconut; eriophyid mite; Aceria-guerreronis